Under‐ice metabolism in a shallow lake in a cold and arid climate. (24th July 2019) - Song, Shuang; Li, Changyou; Shi, Xiaohong; Zhao, Shengnan; Tian, Weidong; Li, Zhijun; Bai, Yila; Cao, Xiaowei; Wang, Qingkai; Huotari, Jussi; Tulonen, Tiina; Uusheimo, Sari; et al.
Abstract: Winter is a long period of the annual cycle of many lakes in the northern hemisphere. Low irradiance, ice, and snow cover cause poor light penetration into the water column of these lakes. Therefore, in northern lakes, respiration often exceeds primary production leading to low dissolved oxygen concentrations. This study aimed to quantify under‐ice metabolic processes during winter in an arid zone lake with little snow cover. This study was carried out in a mid‐latitude lake in Inner Mongolia, northern China. The study lake receives relatively high incoming solar radiation on the ice in mid‐winter, and radiation can penetrate down to the bottom sediment as the lake is shallow and the ice lacks snow cover. Primary production and respiration were estimated during two winters using high‐frequency sensor measurements of dissolved oxygen. To quantify under‐ice metabolic processes, sensors were deployed to different depths. During both winters, sensors collected data every 10 min over several weeks. The amount of solar radiation controlled photosynthesis under ice; temperature and photosynthesis together appeared to control respiration. The balance between gross primary production and ecosystem respiration was especially sensitive to changes in snow cover, and the balance between P and R decreased. Our data suggest that photosynthesis by plankton, submerged plants, and epiphytic algae may continue over winter in shallow lakes in mid‐latitudes when there is no snow cover on the ice, as may occur in arid climates. The continuation of photosynthesis under ice buffers against dissolved oxygen depletion and prevents consequent harmful ecosystem effects.